Improving GSM call completion by call reestablishment. - Phone Lin
Global system for mobile communications (GSM) call reestablishment service allows a mobile station to resume a call in which the radio link has been temporarily interrupted due to interference or bad signal (which is referred to as an interrupted call). This service increases end user satisfaction and network quality perception. We propose analytic models to study the performance for call reestablishment service. Our study indicates that call reestablishment can significantly reduces dropping for interrupted calls
Keywords: GSM call completion; PCS; Analytic models; Call reestablishment; Call reestablishment service; End user satisfaction; Global system for mobile communications; Interference; Interrupted call dropping reduction; Mobile station; Network quality; Performance; Personal communications services; Probability; Radio link